STUDI LITERATUR POTENSI ANTIOKSIDAN DAUN KELOR (MORINGA OLEIFERA L.) TERHADAP HIPERKOLESTEROLEMIA. - Desry Natalia Sidauruk; Lamtama Robintang Simarmata; Dian Sharon Simbolon; Jessica Angelita Lubis; Renny Cherly Cicilia Sitorus (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Hypercholesterolemia is a lipid metabolism disorder characterized by elevated blood cholesterol levels and is a risk factor for cardiovascular disease. Moringa leaves (Moringa oleifera L.) are known to contain various bioactive compounds that have the potential to act as natural antioxidants and play a role in controlling cholesterol levels. This study aims to examine the antioxidant compounds contained in Moringa leaves and their potential in the prevention and management of hypercholesterolemia, based on various published research results. The method used was a literature review by collecting and analyzing relevant scientific articles. The results of the study indicate that Moringa leaves contain flavonoids, polyphenols, quercetin, kaempferol, gallic acid, vitamin C, β-carotene, saponins, and phytosterols, which act as antioxidants. These compounds can inhibit free radical formation, prevent LDL oxidation, enhance the endogenous antioxidant system, and help improve lipid profiles by reducing total and LDL cholesterol levels and increasing HDL levels. Based on the results of this study, Moringa leaves have the potential to be developed as an herbal alternative in the prevention and management of hypercholesterolemia.